Transmission Dynamics of Measles: A Mathematical Model - Dr Arvind kumar yadav, Mamta Raipuriya, (International Journal of Scientific Research and Management (IJSRM), 2017)
In this paper, a mathematical model has been studied the stability of the disease free and endemicequilibrium point and their linear stability analysis have been conducted. The model it has been shown that the disease free and also the endemic equilibrium point are linearly asymptotically stable. From the stability of disease free equilibrium point it can be shown, disease will not spread in the population and the endemic quilibrium point it can be conclude that disease will remain in the population.